Can training improve staff skills with complex trauma?. Issue 2 (2nd July 2019) - Robinson, Paula; Griffith, Emma; Gillmore, Chris
Abstract : Purpose: Studies show that experiences of repeated or complex trauma are very common in patients with severe mental health problems. Unfortunately, many professionals do not routinely ask about abuse, due to concerns about how to ask and respond. There is also a need for frontline staff to be trained in trauma-informed care. The purpose of this paper is to identify the needs of inpatient staff and developed a tailor-made training package. Design/methodology/approach: A training programme was developed from focus-group discussion and delivered to the team. Questionnaires were administered pre-, post-training and at three-month follow-up, to assess changes in knowledge, confidence and worries in the assessment and treatment of complex trauma. Findings: There was an increase in self-reported staff confidence ( p =0.001) and knowledge ( p =0.028) about working with complex trauma and their worries decreased ( p =0.026) between pre- and post-training. Practical implications: In order to sustain the benefits of training for longer, recommendations were made to the service for on-going training, supervision and evaluation. Originality/value: Given the recent interest in complex trauma within the literature (Diagnostic and Statistical Manual of Mental Disorders – Fifth Version (DSM-V); International Statistical Classification of Diseases – 11th Version (ICD-11)), the piloting and development of complex trauma training packages is timely. To the author's knowledge, this is the first published account of complex trauma training for inpatient staff. This paper offers clinical and research implications to services who may want to develop as trauma-informed services within the NHS.